Znaczenie zaangażowanej postawy rodziców w edukację medialną małego dziecka - Iwanicka, Agnieszka (Neodidagmata, 2018)
In recent years, there has been a increase interest meaning of the media in the life of a small children. The reason for this is the constantly decreasing age of media initiation of the youngest and the noticeable, growing role of the media in their lives. Undoubtedly, new information and communication technologies have a significant role in increasing the efficiency of the teaching and learning process, develop key social skills (such as the ability to work in a group, solve problems), but above all they are a great tool to support the child’s development. Their conscious use in the educational and educational process allows children to enter the digital future, equipping them with competences, without which it will be difficult to find young people on the labor market soon. In the article, I ask questions about the role of the family environment in early media education of school-aged children. I wonder how important is the active, committed attitude of parents in shaping the media environment of children, their ways of using information and communication technologies against other standard activities, the time they devote to the media and skills in the use of on-screen media.